Simulation of Temperature Field within an Unsteady Pneumatic System with Constant Volume - Zhu, Dong; Liu, Changhai (IET Conference Proceedings, 2018)
A two-dimension model of a pneumatic system consisting of a constant volume chamber, an orifice and a pipeline is established. The unsteady flow field and temperature profile are simulated with the finite volume method (FVM) for a number of charging-discharging cycles until a negligible temperature change is observed. The minimum temperature on outer surface is found on the orifice. The temperature increases during the first half cycle (charging period) and drops during the second half cycle (discharging period). After a number of cycles, temperatures in most locations within the system do not change with time significantly. This work is expected to help evaluate the operating performance of a pneumatic system involving condensation and evaporation.